Pseudo-arterial Temporary Hemodialysis Catheter Placement in the Left Internal Jugular Vein Ipsilateral to a Preexisting Brachio-axillary Arteriovenous Graft - Onuigbo, Macaulay Amechi Chukwukadibia (Indian J Nephrol, 2020)
Internal jugular vein (IJV) cannulation was originally described by English et al. in 1969 as the safest approach. Carotid artery puncture had an incidence rate of 4–6% before ultrasound guidance. We encountered an unexpected sequence of events following the ultrasound-guided placement of a temporary HD catheter in the left IJV. The postprocedure chest radiograph was misinterpreted as an arterial misplacement, the blood return was correspondingly bright red, and simultaneous blood gas analyses from the left IJV catheter and a right radial artery were near mirror images. Subsequently, a transducer to the catheter showed a clearly venous waveform with a pressure of 40 mmHg. Thus, it was realized that the cacophony of missteps, misjudgments, and misinterpretations was due to the contiguous presence of a functional left brachio-axillary arteriovenous (AV) graft. To our knowledge, this is the first such report of this phenomenon of a pseudo-arterial central venous catheter placement in the IJV.